Enhancing composting efficiency: Impact of microbial consortia on cow manure decomposition - Priyadi, Priyadi; Rahmadi, Rizky; Rochman, Fajar; Dulbari, Dulbari; Sari, Evi Yunita; Buana, Arum Sekar; Sudrajat, Denny; Surahman, Suryansyah (Journal of Degraded and Mining Lands Management, 2025)
Composting organic waste is significantly gaining attention as a sustainable and environmentally friendly material. This is because the use of microorganisms or microbial consortia in the composting process can enhance the quality of compost. Therefore, this study aimed to examine the impact of microbial consortia on cow manure composting efficiency and nutrient content. The experiment was conducted at the Polinela Organic Farm, Department of Food Crop Cultivation. A randomized block design was used with multiple treatments combining fresh cow manure and microbial inoculants, including catalyst, Bacillus, and Trichoderma. The parameters evaluated were the effects of water content, pH, temperature fluctuations, and macronutrient levels on composting, including nitrogen, phosphorus, and potassium. The results showed that microbial consortia significantly improved composting parameters such as moisture retention and temperature as a function of higher doses?of the inoculum. The highest total nitrogen (3.6%) and potassium (1.67%) content were obtained from Trichoderma treatment,?while the highest phosphorus (0.47%) content was obtained from Bacillus treatment. This?implied that microbial consortia could improve the quality and availability of composted nutrients in addition to the effectiveness of agricultural waste management and soil fertility practices. However, more research should be conducted?to determine the optimal microbial mixtures for various conditions of composting and the quality of the best compost produced.